P216 Associations between the psychological health of patients and their informal carers in advanced copd: what are the risk factors for anxiety and depression in patients, carers and patient-carer dyads?. (15th November 2016) - Mi, EZ; Mi, EZ; Mendonca, S; Gardener, AC; Farquhar, MC
Abstract : Introduction: Anxiety and depression (AD) are highly prevalent in patients with advanced COPD and their informal carers, and are associated with lower quality of life and increased healthcare use. Previous studies have postulated risk factors for patient AD in COPD (including dyspnoea, poor functional status and poor self-management) and carer AD (including female gender, insufficient support and high subjective symptom burden). However, little is known about the association between patient and carer AD. We aimed to determine this and factors associated with patient, carer and dyad AD. Methods: Prospective mixed-method interviews with a population-based cohort of 109 pairs of well-characterised advanced COPD patients and their carers. Clinical anxiety and depression (defined as Hospital Anxiety and Depression Scale [HADS] anxiety or depression score >11) were identified and a dichotomous 'psychological morbidity' (PM) variable created (HADS score >11 for either anxiety or depression) due to small sample size. Mann-Whitney U tests and multivariate logistic regression identified factors associated with patient (n = 39) or carer (n = 30) PM. Results: Prevalence of anxiety and depression was 31.2% and 15.6% in patients and 26.6% and 11% in carers respectively. In univariate analysis, patient and carer PM were significantly associated with each other (p = 0.005), with odds ratio 3.388 (95% CI: 1.414–8.118), and mainly disease-related variables and carer characteristics (including poor coping and unmet support needs), respectively. No demographic factors were significantly associated with patient PM but female gender was associated with carer PM. Table 1 shows the results of multivariate analysis. Finally, dyad PM was associated with male patients/female carers, living apart, parent-child relationship, and more exacerbations. Conclusions: For patients, more exacerbations may indicate disease progression resulting in anxiety, fatigue may limit activity leading to social isolation and depression, and poor self-management may increase symptom burden leading to AD. Patient PM could lead to carer PM by increasing carer burden and impairing intra-dyad communication. Our study, with the strength of a prospective approach and recruitment from primary care, highlights the need to assess AD in carers of COPD patients (particularly with AD), to prevent it with more information and support for carers, and for interventions targeting the dyad.